Polymer, preparation method and application thereof, and water-based drilling fluid

By developing a polymer containing dendritic polyester matrix, the problem of insufficient temperature resistance of water-based drilling fluid cutting agent is solved, and excellent cutting and viscosity-enhancing effect is achieved at high temperature, which is suitable for drilling in high-temperature wells construction.

CN119241776APending Publication Date: 2025-01-03CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310805565.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The existing cutting agents for water-based drilling fluids have insufficient temperature resistance, which limits their application in high-temperature wells, resulting in construction problems such as rock carrying difficulties and sand-sand drilling.

Method used

Develop a polymer, including a dendritic polyester matrix and polymer segments grafted on its surface, formed by esterification reaction of polyhydroxy compounds and monocarboxylic acids or monocarboxylic acid esters, with specific structural units, to enhance Its stability and lifting effect at high temperatures.

Benefits of technology

该聚合物在高温环境下保持优异的抗温性能,能够有效提切和增黏钻井液,抗温可达160℃,并且制备过程简便易控制,适合工业化生产。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241776A_ABST
    Figure CN119241776A_ABST
Patent Text Reader

Abstract

The invention relates to the field of petroleum drilling auxiliaries, in particular to a polymer, a preparation method and application thereof and a water-based drilling fluid. The polymer comprises a dendritic polyester matrix and a polymer chain segment grafted on the surface of the dendritic polyester matrix, the dendritic polyester matrix contains a structural unit A from a polyhydroxy compound, a structural unit B from monocarboxylic acid or monocarboxylic ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid and the monocarboxylic ester respectively and independently contain more than two terminal hydroxyl groups; the polymer chain segment contains a structural unit C1, a structural unit C2 and a structural unit D; in the polymer, the weight ratio of the dendritic polyester matrix to the structural unit C1 to the structural unit C2 to the structural unit D is 1: (0.5-50): (0.5-100): (0.5-50). The polymer is used as a water-based drilling fluid additive, has excellent shear-improving and tackifying effects under a high-temperature condition, and can resist the temperature of 160 DEG C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of petroleum drilling additives, and in particular to a polymer, a preparation method and application thereof, and a water-based drilling fluid. Background Art

[0002] The shear force of drilling fluid reflects the strength of the internal spatial network structure of drilling fluid, and can reflect the ability of drilling fluid to suspend solid phases such as drill cuttings and weighting agents. Low shear force of drilling fluid can lead to drilling construction problems such as difficulty in carrying rock, sand settling, drill bit jamming, and drill bit burial. Shearing agent is a key treatment agent for drilling fluid, especially solid-free drilling fluid, which is used to carry rock and suspend solid phase. The commonly used shearing agent is biopolymer xanthan gum (XC), which has a good shearing effect, but its temperature resistance is less than 120°C, which limits its application in high-temperature wells.

[0003] Dendritic polymers are a new type of polymer with a tree-like structure. Their surface is enriched with a large number of functional groups. The polymer molecules are nanometer-sized and have cavities inside. They have a compact structure similar to a sphere in three-dimensional space. Introducing dendritic polymers into the field of petroleum engineering can provide a new means to solve some complex technical problems. At present, the research on dendritic polymers in the field of petroleum engineering is mostly as anti-shear polymers for improving oil field recovery or amine inhibitors for drilling fluids. There is no research on dendritic polymers as shear enhancers for drilling fluids.

[0004] Therefore, developing a new polymer shearing agent based on dendritic polymers is of great significance for expanding the application of dendritic polymers in the oil field, solving the problem of insufficient temperature resistance of existing drilling fluid shearing agents, and better meeting the needs of drilling fluid viscosity increase and shearing under high temperature conditions. Summary of the invention

[0005] Aiming at the problem that the existing shearing agent for water-based drilling fluid has insufficient temperature resistance, the present invention provides a polymer and a preparation method and application thereof as well as water-based drilling fluid.

[0006] In order to achieve the above-mentioned object, the present invention provides a polymer in a first aspect, comprising a dendritic polyester matrix, and a polymer chain segment grafted on the surface of the dendritic polyester matrix;

[0007] The dendritic polyester matrix contains a structural unit A derived from a polyhydroxy compound, a structural unit B derived from a monocarboxylic acid or a monocarboxylic acid ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid, and the monocarboxylic acid ester each independently contain two or more terminal hydroxyl groups;

[0008] The polymer chain segment contains structural unit C1, structural unit C2 and structural unit D; wherein,

[0009] The structural unit C1 is selected from at least one of a structural unit having a structure represented by formula (1), a structural unit having a structure represented by formula (2), and a structural unit having a structure represented by formula (3);

[0010]

[0011] The structural unit C2 is selected from at least one of a structural unit having a structure represented by formula (4), a structural unit having a structure represented by formula (5), and a structural unit having a structure represented by formula (6);

[0012]

[0013]

[0014] The structural unit D is a structural unit having a structure shown in formula (7);

[0015]

[0016] Wherein, R1 and R2 are each independently selected from -H or C1-C3 alkyl; R3, R4, and R5 are each independently selected from -H or C1-C2 alkyl; R6, R7, R9, R 10 R8, R 11 Each independently selected from C1-C2 alkylene; R 12 C6-C 24 Alkyl; R 13 Selected from -H or C1-C2 alkyl; m is an integer of 10-60;

[0017] In the polymer, the weight ratio of the dendritic polyester matrix: the structural unit C1: the structural unit C2: the structural unit D is 1: (0.5-50): (0.5-100): (0.5-50).

[0018] A second aspect of the present invention provides a method for preparing a polymer, comprising:

[0019] Under aqueous polymerization conditions, a dendritic polyester matrix, a first olefinic monomer, a second olefinic monomer and a hydrophobic monomer are polymerized to obtain a polymer;

[0020] The dendritic polyester matrix contains a structural unit A from a polyhydroxy compound, a structural unit B from a monocarboxylic acid or a monocarboxylic acid ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid, and the monocarboxylic acid ester each independently contain two or more terminal hydroxyl groups;

[0021] The first ethylenic monomer is selected from at least one of a monomer having a structure represented by formula (13), a monomer having a structure represented by formula (14), and a monomer having a structure represented by formula (15);

[0022]

[0023]

[0024] The second ethylenic monomer is selected from at least one of a monomer having a structure represented by formula (16), a monomer having a structure represented by formula (17), and a monomer having a structure represented by formula (18);

[0025]

[0026] The hydrophobic monomer is a monomer having a structure shown in formula (19);

[0027]

[0028] Wherein, R1 and R2 are each independently selected from -H or C1-C3 alkyl; R3, R4, and R5 are each independently selected from -H or C1-C2 alkyl; R6, R7, R9, R 10 R8, R 11 Each independently selected from C1-C2 alkylene; R 12 C6-C 24 Alkyl; R 13 Selected from -H or C1-C2 alkyl; m is an integer of 10-60;

[0029] The weight ratio of the dendritic polyester matrix: the first olefinic monomer: the second olefinic monomer: the hydrophobic monomer is 1: (0.5-50): (0.5-100): (0.5-50).

[0030] The third aspect of the present invention provides a polymer obtained by the preparation method described in the second aspect.

[0031] The fourth aspect of the present invention provides the use of the polymer described in the first aspect or the third aspect as a shear enhancing agent in a water-based drilling fluid.

[0032] The fifth aspect of the present invention provides a water-based drilling fluid comprising the polymer described in the first aspect or the third aspect.

[0033] Through the above technical solution, the present invention has the following beneficial effects:

[0034] (1) The polymer provided by the present invention has a dendritic polyester containing a large number of terminal hydroxyl groups as the core, and a long chain containing a specific structural unit is grafted on the surface of the dendritic polyester. The polymer can be dispersed in water and can form a hydrophobic micro-region through hydrophobic association, so that the polymer has a relatively stable three-dimensional grid structure under high temperature environment, reducing the influence of high temperature on the stability of the chain polymer, and thus has excellent temperature resistance, and the temperature resistance reaches 160°C;

[0035] (2) The polymer provided by the present invention can be used as a drilling fluid additive to have excellent shear and viscosity enhancement effects under high temperature conditions;

[0036] (3) The dendritic polyester used to prepare the polymer of the present invention can be synthesized by a one-step reaction, which is simple and easy to obtain; the preparation conditions of the polymer provided by the present invention are mild, the reaction process is easy to control, and it can be prepared by industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is the infrared spectrum of the dendritic polyester HBPE-G2 prepared in the present invention.

[0038] Figure 2 This is the infrared spectrum of polymer P1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0040] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0041] The first aspect of the present invention provides a polymer, comprising a dendritic polyester matrix, and a polymer segment grafted on the surface of the dendritic polyester matrix;

[0042] The dendritic polyester matrix contains a structural unit A derived from a polyhydroxy compound, a structural unit B derived from a monocarboxylic acid or a monocarboxylic acid ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid, and the monocarboxylic acid ester each independently contain two or more terminal hydroxyl groups;

[0043] The polymer chain segment contains structural unit C1, structural unit C2 and structural unit D; wherein,

[0044] The structural unit C1 is selected from at least one of a structural unit having a structure represented by formula (1), a structural unit having a structure represented by formula (2), and a structural unit having a structure represented by formula (3);

[0045]

[0046] The structural unit C2 is selected from at least one of a structural unit having a structure represented by formula (4), a structural unit having a structure represented by formula (5), and a structural unit having a structure represented by formula (6);

[0047]

[0048]

[0049] The structural unit D is a structural unit having a structure shown in formula (7);

[0050]

[0051] Wherein, R1 and R2 are each independently selected from -H or C1-C3 alkyl; R3, R4, and R5 are each independently selected from -H or C1-C2 alkyl; R6, R7, R9, R 10 R8, R 11 Each independently selected from C1-C2 alkylene; R 12 C6-C 24 Alkyl; R 13 Selected from -H or C1-C2 alkyl; m is an integer of 10-60;

[0052] In the polymer, the weight ratio of the dendritic polyester matrix: the structural unit C1: the structural unit C2: the structural unit D is 1: (0.5-50): (0.5-100): (0.5-50).

[0053] According to the present invention, the dendritic polyester matrix, structural unit C1, structural unit C2, and structural unit D in the polymer, on the basis of satisfying the above-mentioned weight ratio relationship, preferably, the weight ratio of the dendritic polyester matrix: structural unit C1: structural unit C2: structural unit D is 1: (0.5-20): (0.5-50): (0.5-20), which can make the polymer have better effect of improving the shear force and viscosity of the drilling fluid and better temperature resistance.

[0054] According to the present invention, by introducing the structural unit C1 into the polymer chain segment grafted on the surface of the dendritic polyester matrix, the polymer can have better water solubility and better adsorption.

[0055] Preferably, the structural unit C1 is selected from at least one of a structural unit having a structure represented by formula (8), a structural unit having a structure represented by formula (9), and a structural unit having a structure represented by formula (10);

[0056]

[0057] In the present invention, it is further preferred that the structural unit C1 is selected from a structural unit having a structure represented by formula (8) and / or a structural unit having a structure represented by formula (10).

[0058] According to the present invention, by introducing the structural unit C2 into the polymer chain segment grafted onto the surface of the dendritic polyester matrix, the polymer can have better temperature resistance and salt resistance.

[0059] Preferably, the structural unit C2 is selected from a structural unit having a structure represented by formula (11) and / or a structural unit having a structure represented by formula (12);

[0060]

[0061] In the present invention, it is further preferred that the structural unit C2 is a structural unit having a structure represented by formula (11).

[0062] According to the present invention, the hydrophobic structural unit D is introduced into the polymer chain segment grafted on the surface of the dendritic polyester matrix, which is conducive to forming a three-dimensional network structure through the hydrophobic association of the hydrophobic chains, so that the polymer has a better shearing effect.

[0063] Preferably, in the structural unit D, R 12 C 12 -C 22 Alkyl; R 13 is -H or methyl; m is an integer of 10-50.

[0064] In the present invention, it is further preferred that in the structural unit D, R 12 C 14 -C 20 Alkyl; R 13 is -H or methyl; m is an integer of 20-40.

[0065] According to the present invention, the dendritic polyester matrix is ​​a polyhydroxy compound containing two or more terminal hydroxyl groups as the core, and the terminal hydroxyl groups on the core are subjected to an esterification reaction with a monocarboxylic acid containing two or more terminal hydroxyl groups (or the terminal hydroxyl groups on the core are subjected to an esterification reaction with a monocarboxylic acid ester containing two or more terminal hydroxyl groups) to obtain a first-generation dendritic polyester. Since the monocarboxylic acid (or monocarboxylic acid ester) used to prepare the first-generation dendritic polyester also contains two or more terminal hydroxyl groups, terminal hydroxyl groups are introduced into the first-generation dendritic polyester formed, so that it can continue to undergo an esterification reaction with a monocarboxylic acid containing two or more terminal hydroxyl groups (or the first-generation dendritic polyester formed can continue to undergo an esterification reaction with a monocarboxylic acid ester containing two or more terminal hydroxyl groups) to obtain a second-generation dendritic polyester. By analogy, third-generation, fourth-generation, fifth-generation, etc. generation dendritic polyesters can be obtained. In the present invention, the generation of the dendritic polyester matrix is ​​n, and preferably n is an integer of 1-5.

[0066] According to the present invention, for the connecting ester groups contained in the dendritic polyester matrix, when the dendritic polyester matrix is ​​obtained by an esterification reaction between a polyhydroxy compound containing two or more terminal hydroxyl groups and a monocarboxylic acid containing two or more terminal hydroxyl groups, the connecting ester groups include ester groups generated by an esterification reaction between the terminal hydroxyl groups in the polyhydroxy compound and the carboxyl groups in the monocarboxylic acid, and ester groups generated by an esterification reaction between the terminal hydroxyl groups contained in the monocarboxylic acid itself and the carboxyl groups; when the dendritic polyester matrix is ​​obtained by an ester exchange reaction between a polyhydroxy compound containing two or more terminal hydroxyl groups and a monocarboxylic acid ester containing two or more terminal hydroxyl groups, the connecting ester groups include ester groups generated by the ester exchange reaction, and ester groups generated by an esterification reaction between the terminal hydroxyl groups contained in the monocarboxylic acid ester itself and the carboxyl groups.

[0067] In the present invention, the terminal hydroxyl group refers to the hydroxyl group at the end of the chain in the compound structure, which can be the end of the main chain of the compound or the end of the side chain of the compound. The terminal hydroxyl group has greater reactivity and is easy to undergo esterification reaction with the carboxyl group.

[0068] According to the present invention, preferably, the polyhydroxy compound is selected from one of pentaerythritol, dipentaerythritol and trimethylolpropane.

[0069] According to the present invention, preferably, the monocarboxylic acid is selected from 2,2-dimethylolpropionic acid and / or 2,2-dimethylolbutanoic acid.

[0070] According to the present invention, preferably, the monocarboxylic acid ester is selected from at least one of methyl 2,2-dihydroxymethylpropionate, ethyl 2,2-dihydroxymethylpropionate, propyl 2,2-dihydroxymethylpropionate, butyl 2,2-dihydroxymethylpropionate, methyl 2,2-dihydroxymethylbutyrate, ethyl 2,2-dihydroxymethylbutyrate, propyl 2,2-dihydroxymethylbutyrate, butyl 2,2-dihydroxymethylbutyrate, methyl N,N-dihydroxyethyl-3-aminopropionate, ethyl N,N-dihydroxyethyl-3-aminopropionate, and butyl N,N-dihydroxyethyl-3-aminopropionate.

[0071] According to one embodiment of the present invention, the dendritic polyester matrix can be prepared by an esterification reaction of the polyhydroxy compound with the monocarboxylic acid using a nuclear one-step method. Specifically, under a protective atmosphere and in the presence of a catalyst, the polyhydroxy compound and the monocarboxylic acid are reacted at 130-150°C for 2-5h, and then the small molecule byproducts in the product are removed under reduced pressure to obtain the dendritic polyester matrix. The catalyst can be selected from trifluoromethanesulfonic acid and / or p-toluenesulfonic acid. In the above preparation process, preferably, the weight ratio of the catalyst: (polyhydroxy compound + monocarboxylic acid) is (0.3-3): 100. By adjusting the feed ratio of the polyhydroxy compound to the monocarboxylic acid, the dendritic polyester matrix of different generations can be obtained, preferably the dendritic polyester matrix of 1-5 generations.

[0072] According to another embodiment of the present invention, the dendritic polyester matrix can be prepared by a nuclear one-step method by transesterifying the polyhydroxy compound with the monocarboxylic acid ester. Specifically, under a protective atmosphere and in the presence of a catalyst, the polyhydroxy compound and the monocarboxylic acid ester are reacted at 120-140°C for 2-5 hours, and a vacuum treatment is performed during the reaction. After the reaction is completed, the vacuum treatment is performed for more than 30 minutes to obtain the dendritic polyester matrix. Wherein, the catalyst can be selected from trifluoromethanesulfonic acid and / or p-toluenesulfonic acid. In the above preparation process, preferably, the weight ratio of the catalyst: (polyhydroxy compound + monocarboxylic acid ester) is (0.3-3): 100. By adjusting the feeding ratio of the polyhydroxy compound and the monocarboxylic acid ester, the dendritic polyester matrix of different generations can be obtained, preferably the dendritic polyester matrix of 1-5 generations.

[0073] According to the present invention, the dendritic polyester matrix makes the polymer formed with it as the core have a dendritic structure. The dendritic polyester matrix is ​​connected to the carbon atom at one end of the polymer chain segment through the methylene adjacent to the terminal hydroxyl contained therein. The polymer provided by the present invention has a dendritic polyester containing a large number of terminal hydroxyl groups as the core, and a long chain containing a specific structural unit is grafted on the surface of the dendritic polyester, so that the polymer has excellent water-based drilling fluid shearing performance, and can still maintain a good shearing and viscosity-increasing effect in a high temperature environment, and the temperature resistance can reach 160°C.

[0074] According to a most preferred embodiment of the present invention, the dendritic polyester matrix in the polymer is a second-generation or third-generation dendritic polyester obtained by esterification of trimethylolpropane and 2,2-dimethylolpropionic acid; the polymer chain segment grafted on the surface of the dendritic polyester matrix contains a structural unit C1 ( )、Structural unit C2( ) and structural unit D( Among them, R 12 C 14 -C 20 Alkyl; R 13 is -H or methyl; m is an integer of 30-40); the weight ratio of the dendritic polyester matrix: structural unit C1: structural unit C2: structural unit D is 1: (5-15): (25-40): (2-10). The polymer of the most preferred embodiment has a further improved shearing and viscosity-enhancing effect on water-based drilling fluid under high temperature conditions.

[0075] A second aspect of the present invention provides a method for preparing a polymer, comprising:

[0076] Under aqueous polymerization conditions, a dendritic polyester matrix, a first olefinic monomer, a second olefinic monomer and a hydrophobic monomer are polymerized to obtain a polymer;

[0077] The dendritic polyester matrix contains a structural unit A from a polyhydroxy compound, a structural unit B from a monocarboxylic acid or a monocarboxylic acid ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid, and the monocarboxylic acid ester each independently contain two or more terminal hydroxyl groups;

[0078] The first ethylenic monomer is selected from at least one of a monomer having a structure represented by formula (13), a monomer having a structure represented by formula (14), and a monomer having a structure represented by formula (15);

[0079]

[0080] The second ethylenic monomer is selected from at least one of a monomer having a structure represented by formula (16), a monomer having a structure represented by formula (17), and a monomer having a structure represented by formula (18);

[0081]

[0082] The hydrophobic monomer is a monomer having a structure shown in formula (19);

[0083]

[0084] Wherein, R1 and R2 are each independently selected from -H or C1-C3 alkyl; R3, R4, and R5 are each independently selected from -H or C1-C2 alkyl; R6, R7, R9, R 10 R8, R 11 Each independently selected from C1-C2 alkylene; R 12 C6-C 24 Alkyl; R 13 Selected from -H or C1-C2 alkyl; m is an integer of 10-60;

[0085] The weight ratio of the dendritic polyester matrix: the first olefinic monomer: the second olefinic monomer: the hydrophobic monomer is 1: (0.5-50): (0.5-100): (0.5-50).

[0086] According to the present invention, in the preparation method of the polymer, the dendritic polyester matrix, the first olefinic monomer, the second olefinic monomer and the hydrophobic monomer, on the basis of satisfying the above-mentioned feeding weight ratio, preferably, the weight ratio of the dendritic polyester matrix: the first olefinic monomer: the second olefinic monomer: the hydrophobic monomer is 1: (0.5-20): (0.5-50): (0.5-20). The above-mentioned preferred feeding ratio can make the prepared polymer have better effect of improving the shear force of drilling fluid and temperature resistance.

[0087] According to the present invention, in the method for preparing the polymer, the first olefinic monomer is a nonionic monomer and can provide at least one of the following structural units having a structure represented by formula (1), a structural unit having a structure represented by formula (2), and a structural unit having a structure represented by formula (3),

[0088]

[0089] Preferably, the first vinyl monomer is selected from at least one of acrylamide, N-vinylformamide and N-vinyl-2-pyrrolidone.

[0090] In the present invention, further preferably, the first vinyl monomer is acrylamide and / or N-vinylformamide.

[0091] According to the present invention, in the method for preparing the polymer, the second ethylenic monomer is an anionic monomer and can provide at least one of the following structural units having a structure represented by formula (4), a structural unit having a structure represented by formula (5), and a structural unit having a structure represented by formula (6),

[0092]

[0093] Preferably, the second ethylenic monomer is selected from 2-acrylamido-2-methylpropanesulfonic acid and / or 2-acryloyloxy-2-methylpropanesulfonic acid.

[0094] In the present invention, further preferably, the second ethylenic monomer is 2-acrylamide-2-methylpropanesulfonic acid.

[0095] According to the present invention, in the method for preparing the polymer, the hydrophobic monomer can provide a structural unit having a structure shown in formula (7):

[0096]

[0097] Preferably, in the structural formula of the hydrophobic monomer, R 12 C 12 -C 22 Alkyl; R 13 is -H or methyl; m is an integer from 10 to 50. Further preferably, R 12 C 14 -C 20 Alkyl; R 13 is -H or methyl; m is an integer of 20-40.

[0098] According to the present invention, in the preparation method of the polymer, the dendritic polyester matrix is ​​a polyhydroxy compound containing two or more terminal hydroxyl groups as the core, and the terminal hydroxyl groups on the core are subjected to an esterification reaction with a monocarboxylic acid containing two or more terminal hydroxyl groups (or the terminal hydroxyl groups on the core are subjected to an esterification reaction with a monocarboxylic acid ester containing two or more terminal hydroxyl groups) to obtain a first-generation dendritic polyester. Since the monocarboxylic acid (or monocarboxylic acid ester) used to prepare the first-generation dendritic polyester also contains two or more terminal hydroxyl groups, terminal hydroxyl groups are introduced into the first-generation dendritic polyester formed, so that it can continue to undergo an esterification reaction with a monocarboxylic acid containing two or more terminal hydroxyl groups (or the first-generation dendritic polyester formed can continue to undergo an esterification reaction with a monocarboxylic acid ester containing two or more terminal hydroxyl groups) to obtain a second-generation dendritic polyester. By analogy, third-generation, fourth-generation, fifth-generation, etc. generation dendritic polyesters can be obtained. In the present invention, the generation of the dendritic polyester matrix is ​​n, and preferably n is an integer of 1-5.

[0099] According to the present invention, for the connecting ester groups contained in the dendritic polyester matrix, when the dendritic polyester matrix is ​​obtained by an esterification reaction between a polyhydroxy compound containing two or more terminal hydroxyl groups and a monocarboxylic acid containing two or more terminal hydroxyl groups, the connecting ester groups include ester groups generated by an esterification reaction between the terminal hydroxyl groups in the polyhydroxy compound and the carboxyl groups in the monocarboxylic acid, and ester groups generated by an esterification reaction between the terminal hydroxyl groups contained in the monocarboxylic acid itself and the carboxyl groups; when the dendritic polyester matrix is ​​obtained by an ester exchange reaction between a polyhydroxy compound containing two or more terminal hydroxyl groups and a monocarboxylic acid ester containing two or more terminal hydroxyl groups, the connecting ester groups include ester groups generated by the ester exchange reaction, and ester groups generated by an esterification reaction between the terminal hydroxyl groups contained in the monocarboxylic acid ester itself and the carboxyl groups.

[0100] In the present invention, the terminal hydroxyl group refers to the hydroxyl group at the end of the chain in the compound structure, which can be the end of the main chain of the compound or the end of the side chain of the compound. The terminal hydroxyl group has greater reactivity and is easy to undergo esterification reaction with the carboxyl group.

[0101] According to the present invention, preferably, the polyhydroxy compound is selected from one of pentaerythritol, dipentaerythritol and trimethylolpropane.

[0102] According to the present invention, preferably, the monocarboxylic acid is selected from 2,2-dimethylolpropionic acid and / or 2,2-dimethylolbutanoic acid.

[0103] According to the present invention, preferably, the monocarboxylic acid ester is selected from at least one of methyl 2,2-dihydroxymethylpropionate, ethyl 2,2-dihydroxymethylpropionate, propyl 2,2-dihydroxymethylpropionate, butyl 2,2-dihydroxymethylpropionate, methyl 2,2-dihydroxymethylbutyrate, ethyl 2,2-dihydroxymethylbutyrate, propyl 2,2-dihydroxymethylbutyrate, butyl 2,2-dihydroxymethylbutyrate, methyl N,N-dihydroxyethyl-3-aminopropionate, ethyl N,N-dihydroxyethyl-3-aminopropionate, and butyl N,N-dihydroxyethyl-3-aminopropionate.

[0104] According to one embodiment of the present invention, the dendritic polyester matrix can be prepared by an esterification reaction of the polyhydroxy compound with the monocarboxylic acid using a nuclear one-step method. Specifically, under a protective atmosphere and in the presence of a catalyst, the polyhydroxy compound and the monocarboxylic acid are reacted at 130-150°C for 2-5h, and then the small molecule byproducts in the product are removed under reduced pressure to obtain the dendritic polyester matrix. The catalyst can be selected from trifluoromethanesulfonic acid and / or p-toluenesulfonic acid. In the above preparation process, preferably, the weight ratio of the catalyst: (polyhydroxy compound + monocarboxylic acid) is (0.3-3): 100. By adjusting the feed ratio of the polyhydroxy compound to the monocarboxylic acid, the dendritic polyester matrix of different generations can be obtained, preferably the dendritic polyester matrix of 1-5 generations.

[0105] According to another embodiment of the present invention, the dendritic polyester matrix can be prepared by a nuclear one-step method by transesterifying the polyhydroxy compound with the monocarboxylic acid ester. Specifically, under a protective atmosphere and in the presence of a catalyst, the polyhydroxy compound and the monocarboxylic acid ester are reacted at 120-140°C for 2-5 hours, and a vacuum treatment is performed during the reaction. After the reaction is completed, the vacuum treatment is performed for more than 30 minutes to obtain the dendritic polyester matrix. Wherein, the catalyst can be selected from trifluoromethanesulfonic acid and / or p-toluenesulfonic acid. In the above preparation process, preferably, the weight ratio of the catalyst: (polyhydroxy compound + monocarboxylic acid ester) is (0.3-3): 100. By adjusting the feeding ratio of the polyhydroxy compound and the monocarboxylic acid ester, the dendritic polyester matrix of different generations can be obtained, preferably the dendritic polyester matrix of 1-5 generations.

[0106] According to the present invention, in the method for preparing the polymer, the polymerization reaction is carried out in an aqueous solution system. Preferably, the weight ratio of (the dendritic polyester matrix + the first olefinic monomer + the second olefinic monomer + the hydrophobic monomer): water is 1:(5-15).

[0107] According to the present invention, the polymerization reaction is initiated by initiator, ultraviolet light or microwave.

[0108] In the present invention, for the polymerization reaction initiated by an initiator, the initiator is preferably a tetravalent cerium salt, and more preferably at least one of ammonium cerium nitrate, ammonium cerium sulfate, ammonium cerium phosphate and cerium sulfate. Preferably, the weight ratio of the dendritic polyester matrix: initiator is 1: (0.01-0.05).

[0109] According to the present invention, the polymerization reaction conditions include: reacting under anaerobic conditions; pH value is 5-9; temperature is 30-50° C.; time is 0.5-8 h.

[0110] According to a specific embodiment of the present invention, the operation process for preparing the polymer includes: adding the dendritic polyester matrix into water for mixing and fully dispersing, and then adding the first olefinic monomer, the second olefinic monomer and the hydrophobic monomer to the obtained mixed solution to obtain a reaction system; adding alkali solution to the reaction system to adjust the pH value to 5-9, and introducing protective gas for deoxygenation; then heating to 30-50°C to initiate a polymerization reaction, and the reaction lasts for 0.5-8h; after the reaction is completed, the obtained product viscous solution is treated with ethanol, dried and crushed in sequence to obtain a polymer product.

[0111] In the present invention, preferably, the alkali solution used to adjust the pH value of the reaction system is an aqueous solution of NaOH and / or KOH.

[0112] In the present invention, the protective gas may be nitrogen, helium, argon, etc., preferably nitrogen.

[0113] The invention carries out polymerization reaction on a specific nonionic first olefinic monomer, an anionic second olefinic monomer, a hydrophobic monomer with a certain molecular chain length and a dendritic polyester containing a large number of terminal hydroxyl groups, and grafts a long chain containing a specific structural unit on the surface of the dendritic polyester, wherein the first olefinic monomer provides a structural unit with adsorptivity, the second olefinic monomer provides a structural unit capable of resisting high-temperature hydrolysis, and the hydrophobic monomer provides a structural unit capable of forming a hydrophobic association effect. The long chain containing the specific structural unit and the dendritic polyester volatilize together, so that the prepared polymer still has excellent shear-enhancing and viscosity-increasing effects in a high-temperature water-based environment, and the prepared polymer has a temperature resistance of up to 160°C.

[0114] The third aspect of the present invention provides a polymer obtained by the preparation method described in the second aspect.

[0115] According to the present invention, the structure and properties of the polymer prepared by the method described in the second aspect are the same as those of the polymer described in the first aspect of the present invention, and will not be described in detail here.

[0116] The fourth aspect of the present invention provides the use of the polymer described in the first aspect or the third aspect as a shear enhancing agent in a water-based drilling fluid.

[0117] The fifth aspect of the present invention provides a water-based drilling fluid comprising the polymer described in the first aspect or the third aspect.

[0118] According to the present invention, the content of the polymer in the water-based drilling fluid is not particularly limited. In some embodiments of the present invention, preferably, in the water-based drilling fluid, the weight ratio of the polymer to the water contained in the water-based drilling fluid is (1-5):100.

[0119] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0120] In the following examples, the weight ratio of the structural units contained in the prepared polymer is calculated based on the feed amount of the raw materials.

[0121] Synthesis of dendritic polyesters of different generations (denoted as HBPE-Gn, where G represents "generation" and n represents the number of generations).

[0122] Take HBPE-G1 as an example to illustrate the preparation process: add 5.36g trimethylolpropane and 16.08g 2,2-dimethylolpropionic acid into a 500mL three-necked flask, purge with nitrogen to remove oxygen and heat, add 0.4g trifluoromethanesulfonic acid, install a water separator, heat to 140°C, react for 3h under nitrogen protection, then vacuum to remove water, cool to below 70°C, add tetrahydrofuran, stir and dissolve, precipitate with n-hexane, pour off n-hexane to obtain HBPE-G1, and then add a certain amount of tetrahydrofuran for standby use (HBPE-G1 content is 50w%). According to the above preparation process, the feed ratio is changed to obtain the dendritic polyesters HBPE-G2 to HBPE-G5 with algebra numbers of 2 to 5.

[0123] The HBPE-G2 prepared above was dried and desolventized and then subjected to infrared spectrum test. The results are as follows: Figure 1 As shown, among them, 3420cm -1 The hydroxyl peak is 2980 cm -1 and 2885cm -1 Methyl and methylene peaks, 1730 cm -1 is the carbonyl peak in the ester group, indicating that a dendritic polyester containing terminal hydroxyl groups has been prepared.

[0124] Example 1

[0125] The preparation of the polymer shearing agent is described in this example.

[0126] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G2 (HBPE-G2 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then acrylamide and N-vinyl formamide, 2-acrylamido-2-methylpropanesulfonic acid, and octadecyl polyoxyethylene methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 45° C., and an aqueous solution of ammonium cerium nitrate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as P1);

[0127] Among them, the weight ratio of the dendritic polyester matrix HBPE-G2: (acrylamide + N-vinyl formamide): 2-acrylamide-2-methylpropane sulfonic acid: octadecyl polyoxyethylene methacrylate: ammonium cerium nitrate: deionized water is 1:8:32:4:0.015:450; the weight ratio of acrylamide: N-vinyl formamide is 1:1;

[0128] In P1, the dendritic polyester matrix HBPE-G2: structural unit C1 ( and The weight ratio of the two is 1:1): structural unit C2 ( ): structural unit D( )’s weight ratio is 1:8:32:4.

[0129] The infrared spectrum test of P1 shows the following results: Figure 2 As shown, 3450cm -1 There is a widely distributed characteristic absorption peak nearby, corresponding to the OH stretching vibration of the terminal hydroxyl group; 1720cm -1 The characteristic absorption peak near 2850cm corresponds to the stretching vibration of the carbonyl C=O bond in the ester structure; -1 and 2952cm -1 The characteristic absorption peak corresponds to the stretching vibration of the CH bond; 770cm -1 The characteristic absorption peak corresponds to the long hydrophobic chain (CH2) n The stretching vibration of shows that the polymerization is successfully initiated and the polymer of the present invention is prepared.

[0130] Example 2

[0131] The preparation of the polymer shearing agent is described in this example.

[0132] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G2 (HBPE-G2 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then acrylamide and N-vinyl formamide, 2-acrylamido-2-methylpropanesulfonic acid, and hexadecyl polyoxyethylene methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 45° C., and an aqueous solution of ammonium cerium nitrate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as P2);

[0133] The weight ratio of the dendritic polyester matrix HBPE-G2: (acrylamide + N-vinyl formamide): 2-acrylamide-2-methylpropanesulfonic acid: hexadecyl polyoxyethylene methacrylate: ammonium cerium nitrate: deionized water is 1:8:32:4:0.015:450; the weight ratio of acrylamide: N-vinyl formamide is 1:1;

[0134] In P2, the dendritic polyester matrix HBPE-G2: structural unit C1 ( The weight ratio of the two is 1:1): structural unit C2 ( ): structural unit D( )’s weight ratio is 1:8:32:4.

[0135] Example 3

[0136] The preparation of the polymer shearing agent is described in this example.

[0137] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G2 (HBPE-G2 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and octadecyl polyoxyethylene methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of ammonium cerium sulfate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 5 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as P3);

[0138] The weight ratio of the dendritic polyester matrix HBPE-G2: acrylamide: 2-acrylamide-2-methylpropane sulfonic acid: octadecyl polyoxyethylene methacrylate: ammonium cerium sulfate: deionized water is 1:6:36:4.2:0.016:500.

[0139] In P3, the dendritic polyester matrix HBPE-G2: structural unit C1 ( ): Structural unit C2( ): structural unit D( )’s weight ratio is 1:6:36:4.2.

[0140] Example 4

[0141] The preparation of the polymer shearing agent is described in this example.

[0142] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G2 (HBPE-G2 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then acrylamide, 2-acrylamide-2-methylpropanesulfonic acid, and hexadecyl polyoxyethylene methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of ammonium cerium sulfate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 5 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as P4);

[0143] The weight ratio of the dendritic polyester matrix HBPE-G2: acrylamide: 2-acrylamide-2-methylpropanesulfonic acid: hexadecyl polyoxyethylene methacrylate: ammonium cerium sulfate: deionized water is 1:6:36:4.2:0.016:500.

[0144] In P4, the dendritic polyester matrix HBPE-G2: structural unit C1 ( ): Structural unit C2( ): structural unit D( )’s weight ratio is 1:6:36:4.2.

[0145] Example 5

[0146] The preparation of the polymer shearing agent is described in this example.

[0147] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G2 (HBPE-G2 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then N,N-dimethylacrylamide, acrylic acid, and dodecyl polyoxyethylene methyl methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50°C, and an aqueous solution of ammonium cerium sulfate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried, and crushed in sequence to obtain a polymer product (denoted as P5);

[0148] The weight ratio of the dendritic polyester matrix HBPE-G2: N,N-dimethylacrylamide: acrylic acid: decaalkyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:25:60:25:0.018:800.

[0149] In P5, the dendritic polyester matrix HBPE-G2: structural unit C1 ( ): Structural unit C2( ): structural unit D( )'s weight ratio is 1:25:60:25.

[0150] Example 6

[0151] The preparation of the polymer shearing agent is described in this example.

[0152] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G2 (HBPE-G2 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then N-vinylacetamide, methacrylic acid, and dodecyl polyoxyethylene methyl methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of ammonium cerium sulfate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried, and crushed in sequence to obtain a polymer product (denoted as P6);

[0153] The weight ratio of the dendritic polyester matrix HBPE-G2: N-vinyl acetamide: methacrylic acid: decanyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:30:55:25:0.018:700.

[0154] In P6, the dendritic polyester matrix HBPE-G2: structural unit C1 ( ): Structural unit C2( ): structural unit D( )’s weight ratio is 1:30:55:25.

[0155] Example 7

[0156] The preparation of the polymer shearing agent is described in this example.

[0157] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G1 (HBPE-G1 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then N,N-dimethylacrylamide, acrylic acid, and dodecyl polyoxyethylene methyl methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50°C, and an aqueous solution of ammonium cerium sulfate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried, and crushed in sequence to obtain a polymer product (denoted as P7);

[0158] Wherein, the weight ratio of the dendritic polyester matrix HBPE-G1: N,N-dimethylacrylamide: acrylic acid: decaprylylpolyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:25:60:25:0.018:800.

[0159] In P7, the dendritic polyester matrix HBPE-G1: structural unit C1 ( ): Structural unit C2( ): structural unit D( )'s weight ratio is 1:25:60:25.

[0160] Example 8

[0161] The preparation of the polymer shearing agent is described in this example.

[0162] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G5 (HBPE-G5 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then N-vinylacetamide, methacrylic acid, and dodecyl polyoxyethylene methyl methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of ammonium cerium phosphate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried, and crushed in sequence to obtain a polymer product (denoted as P8);

[0163] The weight ratio of the dendritic polyester matrix HBPE-G5: N-vinyl acetamide: methacrylic acid: decaalkyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:30:55:25:0.018:700.

[0164] In P8, the dendritic polyester matrix HBPE-G5: structural unit C1 ( ): Structural unit C2( ): structural unit D( )’s weight ratio is 1:30:55:25.

[0165] Comparative Example 1

[0166] Deionized water is added to the reactor, and then N-vinylacetamide, methacrylic acid, and dodecylpolyoxyethylene methyl methacrylate are added, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30 wt % NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of an initiator (ammonium persulfate: sodium bisulfite weight ratio is 1:1) is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried, and crushed in sequence to obtain a polymer product (referred to as D1);

[0167] Wherein, the weight ratio of N-vinylacetamide: methacrylic acid: decanyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 30:55:25:0.018:700.

[0168] Comparative Example 2

[0169] Deionized water was added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G5 (HBPE-G5 content was 50w%) was added to mix, and ultrasonic dispersion was uniformly performed, and then N-vinylacetamide and methacrylic acid were added to the obtained mixed solution, and the mixture was stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution was added to the reaction system to adjust the pH value to 7.0, and nitrogen was introduced into the reactor for deoxygenation; the temperature was raised to 50° C., and an aqueous solution of ammonium cerium phosphate was added under stirring to initiate a polymerization reaction, and the reaction lasted for 4 hours; after the reaction was completed, the reactor temperature was lowered to room temperature, and the obtained product viscous solution was treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as D2);

[0170] The weight ratio of the dendritic polyester matrix HBPE-G5: N-vinyl acetamide: methacrylic acid: ammonium cerium sulfate: deionized water is 1:30:55:0.018:700.

[0171] Comparative Example 3

[0172] Deionized water was added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G5 (HBPE-G5 content was 50w%) was added to mix, and ultrasonic dispersion was uniformly performed, and then methacrylic acid and dodecyl polyoxyethylene methyl methacrylate were added to the obtained mixed solution, and the mixture was stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution was added to the reaction system to adjust the pH value to 7.0, and nitrogen was introduced into the reactor for deoxygenation; the temperature was raised to 50° C., and an aqueous solution of ammonium cerium phosphate was added under stirring to initiate a polymerization reaction, and the reaction lasted for 4 hours; after the reaction was completed, the reactor temperature was lowered to room temperature, and the obtained product viscous solution was treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as D3);

[0173] The weight ratio of the dendritic polyester matrix HBPE-G5: methacrylic acid: decaprylyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:55:25:0.018:700.

[0174] Comparative Example 4

[0175] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G5 (HBPE-G5 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then N-vinylacetamide and dodecyl polyoxyethylene methyl methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of ammonium cerium phosphate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried and crushed in sequence to obtain a polymer product (denoted as D4);

[0176] Wherein, the weight ratio of the dendritic polyester matrix HBPE-G5: N-vinyl acetamide: decanyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:30:25:0.018:700.

[0177] Comparative Example 5

[0178] Deionized water is added to the reactor, and then a tetrahydrofuran solution of dendritic polyester HBPE-G5 (HBPE-G5 content is 50w%) is added to mix, and ultrasonic dispersion is uniformly performed, and then N-vinylacetamide, methacrylic acid, and dodecyl polyoxyethylene methyl methacrylate are added to the obtained mixed solution, and the mixture is stirred and dissolved uniformly to obtain a reaction system; a 30wt% NaOH aqueous solution is added to the reaction system to adjust the pH value to 7.0, and nitrogen is introduced into the reactor for deoxygenation; the temperature is raised to 50° C., and an aqueous solution of ammonium cerium phosphate is added under stirring to initiate a polymerization reaction, and the reaction is continued for 4 hours; after the reaction is completed, the reactor temperature is lowered to room temperature, and the obtained product viscous solution is treated with ethanol, dried, and crushed in sequence to obtain a polymer product (denoted as D5);

[0179] The weight ratio of the dendritic polyester matrix HBPE-G5: N-vinyl acetamide: methacrylic acid: decaalkyl polyoxyethylene methyl methacrylate: ammonium cerium sulfate: deionized water is 1:60:120:60:0.018:450.

[0180] In D5, the dendritic polyester matrix HBPE-G5: structural unit C1 ( ): Structural unit C2( ): structural unit D( )'s weight ratio is 1:60:120:60.

[0181] Comparative Example 6

[0182] The method of Example 8 was followed, except that the dodecyl polyoxyethylene methacrylate was replaced with an equal weight of hexadecyl dimethyl diallyl ammonium chloride. Other conditions were the same as those of Example 8 to obtain a polymer product (denoted as D6).

[0183] Test Case

[0184] The polymers P1-P8, D1-D6 prepared in Examples 1-8 and Comparative Examples 1-6 and a commercially available shear enhancing agent (brand name TQ-1, purchased from Aladdin) were tested to evaluate the shear enhancing and viscosity increasing properties and temperature resistance of the above products.

[0185] 1. Evaluation of cutting performance and temperature resistance

[0186] (1) Measure 300 mL of deionized water, add 1 g of polymers P1-P8, D1-D6 and TQ-1 respectively, stir until dissolved, place in a high-temperature roller furnace, heat-roll age at 160° C. for 16 h, take out and cool to room temperature to obtain a solution to be evaluated.

[0187] (2) Using an electric six-speed rotating viscometer, according to the test procedure specified in GB / T 16783.1-2014 "Field Testing of Drilling Fluids in the Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids", the readings of the rotational viscometer of the above-mentioned solution to be evaluated at 600r / min, 300r / min, 200r / min, 100r / min, 6r / min, and 3r / min are recorded as R 600 , R 300 , R 200 , R 100 , R6, R3, calculate the apparent viscosity AV (AV = R 600 / 2), plastic viscosity PV (PV=R 600 -R 300 ), dynamic shear force YP (YP = 1 / 2 × (2R 300 -R 600 The results are shown in Table 1.

[0188] Table 1

[0189]

[0190] As can be seen from Table 1, the aqueous solution prepared with the polymers P1-P8 provided by the present invention still has high viscosity and shear force after high temperature treatment at 160°C, and has a high viscosity at a low shear rate of 3r / min, indicating that the polymer provided by the present invention has excellent shear and viscosity-increasing effects, and good temperature resistance.

[0191] 2. Evaluation of the viscosity-enhancing and shear-enhancing effects of drilling fluid

[0192] P1-P8, D1-D6 and TQ-1 were used as drilling fluid shearing agents to prepare water-based drilling fluid (drilling fluid composition: 400 mL deionized water + 16 g calcium-based bentonite + 5.6 g sodium carbonate + 12 g shearing agent), which were respectively recorded as F1-F8 and DF1-DF7 (where the shearing agent in DF7 was TQ-1).

[0193] The drilling fluids F1-F8 and DF1-DF7 were placed in a high-temperature roller furnace and aged at 160°C for 16 hours. They were taken out and cooled to room temperature. The rotary viscometer of the drilling fluids after aging was tested by an electric six-speed rotary viscometer according to the test procedure specified in GB / T 16783.1-2014 Field Test of Drilling Fluids in the Petroleum and Natural Gas Industry Part 1: Water-Based Drilling Fluids. The readings at 600r / min, 300r / min, 200r / min, 100r / min, 6r / min, and 3r / min were recorded as R respectively. 600 , R 300 , R 200 , R 100 , R6, R3, calculate the apparent viscosity AV (AV = R 600 / 2), plastic viscosity PV (PV=R 600 -R 300 ), dynamic shear force YP (YP = 1 / 2 × (2R 300 -R 600 The results are shown in Table 2.

[0194] Table 2

[0195]

[0196]

[0197] As can be seen from Table 2, the polymers P1-P8 provided by the present invention have excellent shearing and viscosity-increasing effects on water-based drilling fluids. The prepared water-based drilling fluids F1-F8 have high system structure strength, still have high viscosity and shear force after high temperature treatment at 160°C, and have high viscosity at a low shear rate of 3r / min, which is conducive to maintaining the suspension stability of the drilling fluid at high temperature. In particular, polymers D1-D6 do not meet the polymer structure or composition of the present invention, and their temperature resistance and shearing and viscosity-increasing effects are worse than those of P1-P8.

[0198] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A polymer, characterized in that It includes a dendritic polyester matrix, and a polymer chain segment grafted on the surface of the dendritic polyester matrix; The dendritic polyester matrix contains a structural unit A derived from a polyhydroxy compound, a structural unit B derived from a monocarboxylic acid or a monocarboxylic acid ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid, and the monocarboxylic acid ester each independently contain two or more terminal hydroxyl groups; The polymer chain segment contains structural unit C1, structural unit C2 and structural unit D; wherein, The structural unit C1 is selected from at least one of a structural unit having a structure represented by formula (1), a structural unit having a structure represented by formula (2), and a structural unit having a structure represented by formula (3); The structural unit C2 is selected from at least one of a structural unit having a structure represented by formula (4), a structural unit having a structure represented by formula (5), and a structural unit having a structure represented by formula (6); The structural unit D is a structural unit having a structure shown in formula (7); Wherein, R1 and R2 are each independently selected from -H or C1-C3 alkyl; R3, R4, and R5 are each independently selected from -H or C1-C2 alkyl; R6, R7, R9, R 10 R8, R 11 Each independently selected from C1-C2 alkylene; R 12 C6-C 24 Alkyl; R 13 Selected from -H or C1-C2 alkyl; m is an integer of 10-60; In the polymer, the weight ratio of the dendritic polyester matrix: the structural unit C1: the structural unit C2: the structural unit D is 1: (0.5-50): (0.5-100): (0.5-50).

2. The polymer according to claim 1, wherein In the polymer, the weight ratio of the dendritic polyester matrix: the structural unit C1: the structural unit C2: the structural unit D is 1: (0.5-20): (0.5-50): (0.5-20).

3. The polymer according to claim 1 or 2, wherein The structural unit C1 is selected from at least one of a structural unit having a structure represented by formula (8), a structural unit having a structure represented by formula (9), and a structural unit having a structure represented by formula (10); 4. The polymer according to any one of claims 1 to 3, wherein The structural unit C2 is selected from a structural unit having a structure represented by formula (11) and / or a structural unit having a structure represented by formula (12); 5. The polymer according to any one of claims 1 to 4, wherein In the structural unit D, R 12 C 12 -C 22 Alkyl; R 13 is -H or methyl; m is an integer of 10-50.

6. The polymer according to any one of claims 1 to 5, wherein The polyhydroxy compound is selected from one of pentaerythritol, dipentaerythritol and trimethylolpropane; The monocarboxylic acid is selected from 2,2-dimethylolpropionic acid and / or 2,2-dimethylolbutanoic acid; The monocarboxylic acid ester is selected from at least one of methyl 2,2-dihydroxymethylpropionate, ethyl 2,2-dihydroxymethylpropionate, propyl 2,2-dihydroxymethylpropionate, butyl 2,2-dihydroxymethylpropionate, methyl 2,2-dihydroxymethylbutyrate, ethyl 2,2-dihydroxymethylbutyrate, propyl 2,2-dihydroxymethylbutyrate, butyl 2,2-dihydroxymethylbutyrate, methyl N,N-dihydroxyethyl-3-aminopropionate, ethyl N,N-dihydroxyethyl-3-aminopropionate, and butyl N,N-dihydroxyethyl-3-aminopropionate.

7. A method for preparing a polymer, comprising: Under aqueous polymerization conditions, a dendritic polyester matrix, a first olefinic monomer, a second olefinic monomer and a hydrophobic monomer are polymerized to obtain a polymer; The dendritic polyester matrix contains a structural unit A from a polyhydroxy compound, a structural unit B from a monocarboxylic acid or a monocarboxylic acid ester, and a connecting ester group; wherein the polyhydroxy compound, the monocarboxylic acid, and the monocarboxylic acid ester each independently contain two or more terminal hydroxyl groups; The first ethylenic monomer is selected from at least one of a monomer having a structure represented by formula (13), a monomer having a structure represented by formula (14), and a monomer having a structure represented by formula (15); The second ethylenic monomer is selected from at least one of a monomer having a structure represented by formula (16), a monomer having a structure represented by formula (17), and a monomer having a structure represented by formula (18); The hydrophobic monomer is a monomer having a structure shown in formula (19); Wherein, R1 and R2 are each independently selected from -H or C1-C3 alkyl; R3, R4, and R5 are each independently selected from -H or C1-C2 alkyl; R6, R7, R9, R 10 R8, R 11 Each independently selected from C1-C2 alkylene; R 12 C6-C 24 Alkyl; R 13 Selected from -H or C1-C2 alkyl; m is an integer of 10-60; The weight ratio of the dendritic polyester matrix: the first olefinic monomer: the second olefinic monomer: the hydrophobic monomer is 1: (0.5-50): (0.5-100): (0.5-50).

8. The method according to claim 7, wherein: The weight ratio of the dendritic polyester matrix: the first olefinic monomer: the second olefinic monomer: the hydrophobic monomer is 1: (0.5-20): (0.5-50): (0.5-20).

9. The method according to claim 7 or 8, wherein: The first vinyl monomer is selected from at least one of acrylamide, N-vinylformamide and N-vinyl-2-pyrrolidone.

10. The method according to any one of claims 7 to 9, wherein: The second ethylenic monomer is selected from 2-acrylamido-2-methylpropanesulfonic acid and / or 2-acryloyloxy-2-methylpropanesulfonic acid.

11. The method according to any one of claims 7 to 10, wherein: In the structural formula of the hydrophobic monomer, R 12 C 12 -C 22 Alkyl; R 13 is -H or methyl; m is an integer of 10-50.

12. The method according to any one of claims 7 to 11, wherein: The polyhydroxy compound is selected from one of pentaerythritol, dipentaerythritol and trimethylolpropane; The monocarboxylic acid is selected from 2,2-dimethylolpropionic acid and / or 2,2-dimethylolbutanoic acid; The monocarboxylic acid ester is selected from at least one of methyl 2,2-dihydroxymethylpropionate, ethyl 2,2-dihydroxymethylpropionate, propyl 2,2-dihydroxymethylpropionate, butyl 2,2-dihydroxymethylpropionate, methyl 2,2-dihydroxymethylbutyrate, ethyl 2,2-dihydroxymethylbutyrate, propyl 2,2-dihydroxymethylbutyrate, butyl 2,2-dihydroxymethylbutyrate, methyl N,N-dihydroxyethyl-3-aminopropionate, ethyl N,N-dihydroxyethyl-3-aminopropionate, and butyl N,N-dihydroxyethyl-3-aminopropionate.

13. The method according to any one of claims 7 to 12, wherein: The polymerization reaction is initiated by an initiator, ultraviolet light or microwave. Preferably, in the polymerization initiated by the initiator, the initiator is a tetravalent cerium salt, more preferably at least one of ammonium cerium nitrate, ammonium cerium sulfate, ammonium cerium phosphate and cerium sulfate.

14. The method according to any one of claims 7 to 13, wherein: The polymerization reaction conditions include: reacting under anaerobic conditions; pH of 5-9; temperature of 30-50° C.; and time of 0.5-8 h.

15. A polymer obtained by the preparation method according to any one of claims 7 to 14.

16. Use of the polymer according to any one of claims 1 to 7 and 16 as a shear enhancing agent in water-based drilling fluid.

17. A water-based drilling fluid comprising the polymer according to any one of claims 1 to 6 and 15.

18. The water-based drilling fluid according to claim 17, wherein: The weight ratio of the polymer to the water contained in the water-based drilling fluid is (1-5):100.